Evolving for Creativity: Maximizing Complexity in a Self-organized Multi-particle System - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (10th European Conference on Artificial Life (ECAL'09))

Robotic Organisms: Artificial Homeostatic Hormone System and Virtual Embryogenesis as Examples for Adaptive Reaction-Diffusion Controllers - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Thenius, Rona; Fitch, Robert (Robotic Organisms: Artificial Homeostatic Hormone System and Virtual Embryogenesis as Examples)

Die Europäische Genossenschaft (SCE) auf dem Prüfstand - Krimphove, Dieter (Zeitschrift für das gesamte Genossenschaftswesen ZFgG)

BEECLUST: A Swarm Algorithm Derived from Honeybees - Hamann, Heiko; Schmickl, Thomas (Bio-inspired Computing and Communication Networks)

Evolving a novel bio-inspired controller in reconfigurable robots - Hamann, Heiko; Karsai, Istvan; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Thenius, Ronald; Kampis, Gyoergy; Szathmary, Eoers (Advances in Artificial Life, 10th European Conference, ECAL 2009)

Embodiment of Honeybee's Thermotaxis in a Mobile Robot Swarm - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl; Thenius, Ronald; Kengyel, Daniela (10th European Conference on Artificial Life (ECAL'09))

Explaining Emergent Behavior in a Swarm System Based on an Inversion of the Fluctuation Theorem - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (Advances in Artificial Life, ECAL 2011: Proceedings of the 11th European Conference on the Synthesis and Simulation of Living Systems)

Major Feedback Loops Supporting Artificial Evolution in Multi-modular Robotics - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Winkler, Lutz (New Horizons in Evolutionary Robotics)

Modelling a hormone-inspired controller for individual- and multi-modular robotic systems - Schmickl, Thomas; Hamann, Heiko; Crailsheim, Karl (Mathematical and Computer Modelling of Dynamical Systems)

Erweiterter Gestaltungspielraum für Schulen. Welche Veränderungen beschreiben Schulleiterinnen und Schulleiter in ihrem beruflichen Selbstverständnis? - Gerick, Julia; Bloh, Bea

Wiki-Einsatz im Deutschunterricht - Mit neuen Technologien kooperatives Lernen unterstützen - Anskeit, Nadine; Eickelmann, Birgit (Unterrichtsqualität sichern – Grundschule)

EduSummIT 2011: Restructuring educational systems to move into the digital age - Davis, Niki; Eickelmann, Birgit; Patru, Mariana; Schulz-Zander, Renate; Dzvimbo, Peter

Editorial. Technology to enhance learning: Problems and Promises - Eickelmann, Birgit (Journal for Educational Research Online/Journal für Bildungsforschung Online)

Mehr Gerechtigkeit durch Zentralabitur? – Analysen einer Lehrerbefragung in NRW - Lorenz, Ramonda; Kahnert, Julia; Eickelmann, Birgit; Bos, Wilfried (Zeitschrift Schul-Management)

Das Zentralabitur in Nordrhein-Westfalen aus der Lehrerperspektive. Veränderungen für den Unterricht - Eickelmann, Birgit; Kahnert, Julia; Lorenz, Ramona; Bos, Wilfried (SchulVerwaltung NRW)

Messung computer- und informationsbezogener Kompetenzen von Schülerinnen und Schülern als Schlüsselkompetenz im 21. Jahrhundert - Eickelmann, Birgit; Bos, Wilfried (Zeitschrift Medienimpulse)

Learners' identity negotiations and beliefs about pronunciation in study abroad contexts - Müller, Mareike
This dissertation explores learner beliefs about pronunciation and their interaction with identity negotiations in a study-abroad context. Current research on studying abroad has experienced a wave of interest in learner-centered questions, gradually moving away from the narrow focus on students’ linguistic development. In particular, the effects of study abroad on learner identities have attracted attention, revealing the impact of the dispositions of individuals, as well as of interlocutors, on the language learning process. The realm of speaking, especially with regard to pronunciation research, however, has hardly benefited from this interest in the individual perspectives of sojourners. Existing studies merely measure the extent to which learners appropriate native-like accents, resulting in partly inconsistent findings with limited insight into individual learning processes and factors. I thus adopt a different focus by qualitatively investigating the interplay between sojourners’ beliefs about pronunciation and their identity constructions and negotiations. My research is based on five case studies of Canadian learners of German. Each research subject has attended a German university for one or two semesters. In applying narrative inquiry as a research tool for both the within- and cross-case analyses, I investigate participants’ accounts in interviews and e-journals, as conducted at different stages throughout the first sojourn term. Poststructuralist-constructivist conceptualizations of learner identities and beliefs guide the data analysis and interpretation. The results of the holistic and categorical content analyses give insight into the intricate relationship between beliefs about pronunciation and learners’ identity work. In their narratives, learners appear to actively use pronunciation as a tool to construct identity facets in correspondence to specific communities of practice, giving meaning to their investment in the sojourn experience. This process of mediating between different identity constructions appears to be highly complex and partially conflict-laden. The participants’ beliefs and reported learning behaviours are interconnected with their definitions of learning goals, which draw on native-speaker ideals to different extents and with varying results. These orientations are in turn related to the subjects’ degrees of critical language awareness, the latter a factor that appears to play a vital role in shaping the ability of learners to take advantage of learning opportunities. In assessing participants’ learning objectives and their readiness to reflect upon their beliefs and orientations, my study also sheds light on the influence of different learning factor constellations on intercultural learning. The results indicate that unidirectional cause-and-effect relationships cannot be drawn between learners’ beliefs about pronunciation and their abilities to approach their roles as intercultural speakers in sojourn environments. My study rather underlines the importance of illuminating individual learning experiences in their idiosyncrasies and complexities, which may lead to a stronger consideration of learners’ subjective stances in both research and teaching practice. The findings of my study suggest that the primary way that language pedagogy can thus foster the ability to engage in intercultural encounters is by helping learners to become aware of their subjective stances, their self-constructions, and the influence of those on the learning process. Therefore, developing the ability and willingness to critically reflect is crucial, especially with regard to pronunciation. In illuminating the intricate nature of learner beliefs and their influence on the learning process, my study demonstrates the importance of qualitative, emic research into the acquisition of L2 pronunciation.

Bicriteria-Approximation für das k-Median-Clustering mit Bregman-Divergenzen - Böttger, Timm

Situativ trainierte Regeln zur Ablaufsteuerung in Fertigungssystemen und ihre Integration in Simulationssysteme - Aufenanger, Mark

Internationale Standortwahl als strategisches Logistikproblem - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)